Presence of cytomegalovirus in the perilymphatic fluid of patients with profound sensorineural hearing loss caused by congenital cytomegalovirus infection. (1st February 2016) - Ogawa, Hiroshi; Matsui, Takamichi; Baba, Yoko; Yamada, Naoko; Suzuki, Yukie; Suzutani, Tatsuo
Abstract: Conclusion : Not all patients diagnosed with congenital infection using umbilical cord assay were found to be positive for CMV-DNA by perilymphatic fluid assay. In addition, a CMV-DNA-positive result was observed in one patient who had not been diagnosed with congenital infection. Sampling of perilymphatic fluid from a large population of patients with congenital SNHL caused by congenital CMV infection or of unknown etiology is required to determine the prevalence of CMV-related profound HL. Objectives : Sensorineural hearing loss (SNHL) is one of the most frequent manifestations in patients with congenital cytomegalovirus (CMV) infection. Using dried umbilical cord, a PCR-based assay was recently developed for the retrospective detection of congenital CMV infection. This study analyzed the presence of CMV in the perilymphatic fluid and evaluated differences in the effect of cochlear implantation between CMV-positive and -negative groups. Method : Perilymphatic fluid was collected from each patient at the time of cochlear implantation and analyzed for the presence of CMV using a PCR method. Results : The perilymphatic fluid in two of the five patients suffering from congenital CMV infection and in one of the 17 patients without congenital CMV infection was found to be positive for CMV.